A new species of Rhinogobius (Pisces: Gobiidae), with analyses of its DNA barcode - Xia, Jian-Hong; Wu, Han-Lin; Li, Chen-Hong; Wu, Yuan-Qi; Liu, Su-Han (Zootaxa, 2018)
The genus Rhinogobius Gill 1859 is widely distributed in fresh waters along the Western Pacific coast of tropical and temperate Asia. A new species, Rhinogobius maxillivirgatus, is described from Anhui Province in Eastern China. This species can be differentiated from all congeners by a combination of the following characters: up to 6 longitudinal brown to black stripes along the side of the body; pectoral-fin rays modally 14; predorsal scale series 5–9; lateral scale series 28–30; transverse scale series 6–7; branchiostegal membrane with about 20 red round spots in males; and 2 black oblique stripes parallel along the upper jaw on the anterior portion of the cheek. Analyzing sequences of cytochrome c oxidase subunit I revealed that the new species is closely related to, but distinct, from Rhinogobius wuyanlingensis.